1993
DOI: 10.1161/01.hyp.22.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Effects on blood pressure of omega 3 fats in subjects at increased risk of cardiovascular disease.

Abstract: This study was conducted to compare the effects of o>3 fatty acids, taken as fish or fish-oil supplements in the setting of a high-or low-fat dietary background, on blood pressure and heart rate in men with moderate cardiovascular risks. One hundred twenty men were randomly allocated to five high-fat (40% of daily energy) and two low-fat (30% of energy) groups to undertake a 12-week dietary intervention period involving fish, fish oil, or a combination of these. Sodium intake was restricted to less than 90 mmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
(19 reference statements)
1
23
0
1
Order By: Relevance
“…rate similar to those seen in the present study have been associated with consumption of fish oils or fish in humans, 2,15 raising the likelihood of an autonomic/cardiac component to the antihypertensive effect. In addition, it is worth noting that in animal studies, 3 fatty acids are incorporated into myocardial cells and have potent antiarrhythmic effects.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…rate similar to those seen in the present study have been associated with consumption of fish oils or fish in humans, 2,15 raising the likelihood of an autonomic/cardiac component to the antihypertensive effect. In addition, it is worth noting that in animal studies, 3 fatty acids are incorporated into myocardial cells and have potent antiarrhythmic effects.…”
Section: Discussionsupporting
confidence: 85%
“…These same subjects were offered a weight-loss program on completion of the study. Participants taking fish followed diets similar to one of our previous studies 15,16 and were instructed to eat 1 fish meal daily. A selection of previously analyzed fish from the same batch was supplied free of cost.…”
Section: Dietary Education and Interventionmentioning
confidence: 99%
“…33 Reductions in HR similar to those seen in the present study have been reported after the consumption of fish or fish oil supplements. 12,34 We have shown a decrease of 3.1Ϯ1.4 bpm (Pϭ0.036) in 24-hour and 4.2Ϯ1.6 bpm (Pϭ0.013) in daytime HR after daily consumption of fish for 16 weeks in overweight, treated hypertensives. 15 The reductions in mean 24-hour, daytime, and nighttime HR with DHA in the present study were significant and comparable to those reported previously.…”
Section: Discussionmentioning
confidence: 83%
“…In parallel intervention trials, a modest reduction in blood pressure was achievable by fish consumption in patients with hypertension (81,82). In normotensive subjects, no reduction in blood pressure during fish intake was recorded (78,83,84).…”
Section: Fish and Blood Pressurementioning
confidence: 99%